2019
DOI: 10.1002/mabi.201800347
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals (CNCs) Induced Crystallization of Polyvinyl Alcohol (PVA) Super Performing Nanocomposite Films

Abstract: This study is aimed to explore the properties of cellulose nanocrystals (CNC)/polyvinyl alcohol (PVA) composite films with and without 1,2,3,4‐butane tetracarboxylic acid (BTCA), a nontoxic crosslinker. CNC and CNC‐PVA nanocomposite films are prepared using solution‐casting technique. Differential scanning calorimetry (DSC) analyses show that crosslinking increased the glass transition temperature but reduced the melting temperature and crystallinity. Furthermore, high CNC concentrations in the PVA matrix inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…2,45 However, agglomeration of nanocellulose will take place after incorporating excessive content to matrix, resulting in TS decrease. 46,47 From the Figure 3(b), we observed that adding nanocellulose decreases the EB of composite films and the negative effect of CMCNCs on the toughness of the composite film is greater than that of CMCNFs at the same time. Generally, to increase the TS by adding rigid filler is at the cost of toughness.…”
Section: Characterization Of Cmc a Cmc B Cmcnfs And Cmcncsmentioning
confidence: 88%
“…2,45 However, agglomeration of nanocellulose will take place after incorporating excessive content to matrix, resulting in TS decrease. 46,47 From the Figure 3(b), we observed that adding nanocellulose decreases the EB of composite films and the negative effect of CMCNCs on the toughness of the composite film is greater than that of CMCNFs at the same time. Generally, to increase the TS by adding rigid filler is at the cost of toughness.…”
Section: Characterization Of Cmc a Cmc B Cmcnfs And Cmcncsmentioning
confidence: 88%
“…CNC is one of the most suitable materials for enhancing properties of composite materials [ 15 , 16 ]. CNC, consistent with the required food packaging features especially strength and barrier properties, however, One notable disadvantage of CNC is its low resistance to moisture and in the deterioration in mechanical properties of films made from CNC when exposed to moisture [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylic acids, particularly polycarboxylic acid, have been shown to be good cellulose crosslinking agents [ 32 , 33 , 34 ]. SHP is a most effective catalyst for catalyzing a reaction with BTCA [ 35 ] in a previous paper we demonstrate the effect of BTCA on CNC and CNC-poly vinyl alcohol film properties [ 16 ]. This nontoxic crosslinking method serves the textile industry in crosslinking cotton cellulose to improve anti-pilling, wrinkle recovery, antimicrobial, water repelling, and flame-retarding properties of the cotton fabric [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] Ben Shalom et al prepared PVA/cellulose nanocrystals (CNCs) nanocomposite and found that CNC acting as a nucleating agent could increase the crystallinity of PVA at a low CNC content. [ 13 ] He et al fabricated PVA/graphitic carbonitride (g‐C 3 N 4 ) nanocomposites by solution casting method. The results showed that the glass transition temperature, crystallinity, and mechanical performance of PVA were enhanced by the introduction of g‐C 3 N 4 nanosheets.…”
Section: Introductionmentioning
confidence: 99%